The Implementation of Al-Ghazali's Concept of Adab Before Knowledge in the School Culture of SMP GPI Solokan Jeruk - Anggi Nurmalita; Tryana Hafilda; Adi Sukma Barkah; Muhammad Luthfi Dzulfikar; Nurhilal Ahmad Fathin; Hasan Basri (The Future of Education Journal, 2026)
This research is motivated by the critical importance of strengthening students' character and morality amidst modern moral challenges, where the aspect of adab (etiquette/morals) is often neglected in pursuit of purely academic achievements. Al-Ghazali's epistemological thought on the principle of "adab before knowledge" offers a fundamental resolution to balance intellectual and spiritual intelligence within the Islamic education ecosystem. This study aims to analyze in depth the implementation of Al-Ghazali’s concept of "adab before knowledge," as manifested in the school culture at SMP GPI Solokan Jeruk. The research method employed is a descriptive qualitative approach with a case study design. Informants were selected using a purposive sampling technique, comprising the school principal, Islamic Education (PAI) teachers, classroom teachers, and student representatives. Field data collection was gathered through in-depth interviews, direct participant observation of school activities, and documentation studies. Data validity and the originality of activities were tested through source and method triangulation, including the utilization of authentic visual documentation (photographs) taken during the classroom learning and adab-habituation processes. The data analysis technique follows the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that SMP GPI Solokan Jeruk internalizes Al-Ghazali's concept of adab into three dimensions of school culture: (1) the physical artifact dimension through the visualization of Islamic moral messages around the school environment, (2) the espoused values dimension through daily habits such as handshaking (bersalaman), reciting prayers/Asmaul Husna before studying, and performing congregational prayers, and (3) the basic assumption dimension reflected in the humanistic-spiritualistic teacher-student relationship patterns in class. Visual documentation evidence confirms the direct integration of adab values that frame the knowledge transfer interaction. In conclusion, the school culture at SMP GPI Solokan Jeruk successfully reactualizes Al-Ghazali’s classical thought by positioning moral readiness as the core foundation before knowledge transfer takes place.